Optimizing mRNA-Loaded Lipid Nanoparticles as a Potential Tool for Protein-Replacement Therapy - Gambaro, Rocío Celeste (2024)
Lipid nanoparticles (LNPs) tailored for mRNA delivery were optimized to serve as a platform for treating metabolic diseases. Four distinct lipid mixes (LMs) were formulated by modifying various components: LM1 (ALC-0315/DSPC/Cholesterol/ALC-0159), LM2 (ALC-0315/DOPE/Cholesterol/ALC-0159), LM3 (ALC-0315/DSPC/Cholesterol/DMG-PEG2k), and LM4 (DLin-MC3-DMA/DSPC/Cholesterol/ALC-0159). LNPs exhibited stability and homogeneity with a mean size of 75 to 90 nm, confirmed by cryo-TEM and SAXS studies. High mRNA encapsulation (95–100%) was achieved. LNPs effectively delivered EGFP-encoding mRNA to HepG2 and DC2.4 cell lines. LNPs induced cytokine secretion from human peripheral blood mononuclear cells (PBMCs), revealing that LM1, LM2, and LM4 induced 1.5- to 4-fold increases in IL-8, TNF-α, and MCP-1 levels, while LM3 showed minimal changes. Reporter mRNA expression was observed in LNP-treated PBMCs. Hemotoxicity studies confirmed formulation biocompatibility with values below 2%. In vivo biodistribution in mice post intramuscular injection showed significant mRNA expression, mainly in the liver. The modification of LNP components influenced reactogenicity, inflammatory response, and mRNA expression, offering a promising platform for selecting less reactogenic carriers suitable for repetitive dosing in metabolic disease treatment.